Text and Artifact in the Religions of Mediterranean Antiquity : Essays in Honour of Peter Richardson. - Wilson, Stephen G. (Wilfrid Laurier University Press, 2006)
Can archaeological remains be made to "speak" when brought into conjunction with texts? Can written remains, on stone or papyrus, shed light on the parables of Jesus, or on the Jewish view of afterlife? What are the limits to the use of artifactual data, and when is the value overstated? Text and Artifact addresses the complex and intriguing issue of how primary religious texts from the ancient Mediterranean world are illuminated by, and in turn illuminate, the ever-increasing amount of artifactual evidence available from the surrounding world. The book honours Peter Richardson, and the fir.